A Knight’s Illness / A Knight as Illness – The Function of Syphilis in Erasmus of Rotterdam’s Coniugum impar (1529) - REIFF, Lea (Anafora, 2023)
Syphilis is thematized in multiple dialogues of Erasmus’s Colloquia familiaria. Perceived as a new disease at the end of the fifteenth century, it challenges contemporary observers in defining its place within a framework of established, theologically grounded patterns of thought and knowledge as well as corresponding interpretive frames. These difficulties become apparent in the multitude of designations ascribed to the new disease, which manifest various interpretive approaches – a state of affairs Erasmus’s dialogue “Ἄγαμος γάμος sive Coniugum impar” (1529) alludes to. This paper shows how a range of meanings previously ascribed to leprosy is partially transferred to the new disease through constant comparison, differentiation, and amplification. The use of leprosy as an interpretant of syphilis enables a representation of the diseased body as sinful and morally corrupt. Syphilis thus functions as a visible external sign of the internal moral decay of the diseased bridegroom, whose marriage is discussed in the “Coniugum impar”. Historically and polemically, this dialogue is read as a contribution to a literary controversy between Erasmus and Heinrich Eppendorf, which dates back to a dispute between Erasmus and Ulrich von Hutten in 1522/23. It will be shown how the dialogue’s syphilitic bridegroom alludes to Hutten, his writings and self-stylizations and, thus, discredits Eppendorf’s purported role model. Allegorically, the syphilitic bridegroom also serves to brand the Free Imperial Knights of the Holy Roman Empire as a specific class as morally corrupted.